2016
DOI: 10.1115/1.4034036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Single Point Incremental Forming on Mechanical Properties and Chain Orientation in Thermoplastic Polymers

Abstract: Incremental forming of thermoplastic surfaces has recently received significant interest due to the potential for simultaneous reduction in thermal energy consumption and in part-shape specific tooling. This paper examines the mechanical properties and the chain orientation of the formed material in single point incremental forming (SPIF) of amorphous polyvinyl chloride (PVC) and semicrystalline polyamide sheets. Tensile and stress relaxation properties of the formed polymers are compared to those of the unfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The plastic forming processes affect the post-forming properties of the thermoplastics and thus, influence the service performance of the formed components [ 20 ]. The early investigation on this topic in ISF was undertaken by Devarpanah et al [ 21 ]. They, keeping the strain to a fixed value, reported that the mechanical deformation causes a reduction in the tensile yield strength and tensile modulus, while an increase in the tensile ductility and ultimate tensile strength.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The plastic forming processes affect the post-forming properties of the thermoplastics and thus, influence the service performance of the formed components [ 20 ]. The early investigation on this topic in ISF was undertaken by Devarpanah et al [ 21 ]. They, keeping the strain to a fixed value, reported that the mechanical deformation causes a reduction in the tensile yield strength and tensile modulus, while an increase in the tensile ductility and ultimate tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…As regard the correlation between the process parameters and post-forming properties, the nature and degree of their effects are found to be material dependent [ 18 ]. From the structural analyses, they revealed that the deformation reorients the molecular chains, and further, voids are formed whose density increases with increasing of the step size, thereby causing a loss of post-forming yield strength [ 18 , 21 ]. Lozano-Sánchez [ 22 ] further studied the orientation of molecular chains in the formed polymers and clarified that the chains on the inner surface are preferentially aligned in the horizontal feed direction, reasoning to tool’s shearing action, while those on the outer surface are pulled downwards representing the dominant effect of sheet stretching.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Davarpanah et al [67] found the increase of void density in the formed PLA material can lead to the enhanced formability. In other studies [81,82], the authors observed there is a change in orientation of crystalline lamella and molecular chain orientation in thermoplastics due to the deformation of ISF process with a slight change in the total degree of crystallinity. The schematic for the orientation change in ISF could be presented as Fig.…”
Section: Microstructure Evolution Under Deformationmentioning
confidence: 80%